Platycodon D protects human nasal epithelial cells from pyroptosis through the Nrf2/HO-1/ROS signaling cascade in chronic rhinosinusitis - Ruizhi Wang; Yongchun Wang; He Liu; Jinxiang Zhu; Caishan Fang; Weizhen Xu; Zesheng Lu; Yajie Yan; Weiping He; Yan Ruan; Min Zhou (BMC, 2024)
Abstract Background Pyroptosis has been demonstrated being closely associated with the inflammatory progression in chronic rhinosinusitis (CRS). However, platycodon D (PLD) has emerged as a key anti-inflammatory mediator in the inflammatory progression of various respiratory diseases. This study aims at investigating whether PLD could reduce inflammatory progression of CRS by inhibiting pyroptosis. Methods Nasal mucosal tissues from patients with CRS and the control group (simple nasal septal deviation) were analyzed for morphological difference using hematoxylin & eosin staining and for the expression of pyroptosis-related makers by immunofluorescence (IF). Human nasal epithelial cells (HNEpCs) were cultured and co-stimulated with lipopolysaccharide (LPS)/adenosine triphosphate (ATP) to construct an in vitro cellular model simulating CRS. After pretreatment with PLD, EthD-I staining, TUNEL staining, transmission electron microscopy (TEM), and GSDMD-NT detection were performed to evaluate pyroptosis markers. The NLRP3 inflammasome was detected by IF and western blotting (WB). Reactive oxygen species (ROS) were detected by H2DCFDA staining, and mitochondrial membrane potential was evaluated by JC-1 staining. Mitochondrial morphology and structure were observed using TEM. The Nrf2/HO-1 antioxidant signaling pathway was detected using WB. Results The nasal mucosa structure of patients with CRS exhibited significant damage, with a marked increase in the expression of pyroptosis-related proteins compared with the control group. LPS/ATP co-stimulation resulted in an increased expression of IL-18 and IL-1β in HNEpCs, causing significant damage to nuclear and cell membranes, GSDMD-NT accumulation around the cell membrane, and intracellular NLRP3 inflammasome activation. Furthermore, it led to increased ROS expression, significantly decreased mitochondrial membrane potential, and damaged mitochondrial structure. However, pretreatment with PLD significantly reversed the aforementioned trends and activated the Nrf2/HO-1 antioxidant signaling pathway. Conclusions The results of this study confirm that NLRP3-mediated pyroptosis plays a crucial role in the pathological process of nasal mucosal impairment in patients with CRS. PLD inhibits NLRP3-mediated pyroptosis, preventing inflammatory damage in HNEpCs of patients with CRS by activating the Nrf2/HO-1 antioxidant signaling pathway, which in turn reduces ROS production and ameliorates mitochondrial damage.